Manfaat Air Bagi Tumbuhan: Perspektif Al-Qur’an dan Sains - Ahlam Suskha; Rusydi AM; Urwatul Wusqa (Institut Agama Islam Negeri (IAIN) Curup, 2020)
The Benefits of Water for Plants: the Perspectives of Al-Qur’an and ScienceWater is the main element of life. The existence of water is fundamentally vital for creatures on earth, especially for plants which require water to grow. In the Qur’an, many verses discuss water, such as ethical principles with respect to the importance of water and its benefits for life. This study aimed to discuss the benefits of water for living things, especially plants based on the Qur’anic guidance and further compared with scientific theories. This study used the thematic interpretation method (mawdhu'i) with the thematic term model. The focus of this studywas the Qur’anic verses related to water, especially the word water associated with plants. This study showed that the word water (الماء) is repeated 63 times in 41 surahs of the Qur’an, with someassociated words, namely anzala (lowering), sabba (pouring out), asqa (watering / giving drink), ahya (reviving) and akhraja (spawning). The benefits of water for plants according to the Qur'an are ahya (reviving), as found in the QS. Al-An'am: 99. According to science, there are many functions of water for plants such as the main constituent of protoplasm and being a solvent for nutrients needed by plants